A diffusion‐based neurite length‐sensing mechanism involved in neuronal symmetry breaking - Michinori Toriyama; Yuichi Sakumura; Tadayuki Shimada; Shin Ishii; Naoyuki Inagaki (Molecular Systems Biology, 2010)
Abstract Although there has been significant progress in understanding the molecular signals that change cell morphology, mechanisms that cells use to monitor their size and length to regulate their morphology remain elusive. Previous studies suggest that polarizing cultured hippocampal neurons can sense neurite length, identify the longest neurite, and induce its subsequent outgrowth for axonogenesis. We observed that shootin1, a key regulator of axon outgrowth and neuronal polarization, accumulates in neurite tips in a neurite length‐dependent manner; here, the property of cell length is translated into shootin1 signals. Quantitative live cell imaging combined with modeling analyses revealed that intraneuritic anterograde transport and retrograde diffusion of shootin1 account for its neurite length‐dependent accumulation. Our quantitative model further explains that the length‐dependent shootin1 accumulation, together with shootin1‐dependent neurite outgrowth, constitutes a positive feedback loop that amplifies stochastic fluctuations of shootin1 signals, thereby generating an asymmetric signal for axon specification and neuronal symmetry breaking.